Pharmacotherapy of patients with metastatic renal-cell carcinoma – algorithm vs. Polish reality[Polish version: Leczenie farmakologiczne chorych na rozsianego raka nerki – algorytm a polskie realia p. 299] - Żołnierek, Jakub (Contemporary Oncology/Współczesna Onkologia, 2011)
Pharmacotherapy is currently used mainly for palliative treatment of renal cell carcinoma and, less frequently, in locally advanced unresectable renal tumors. The introduction of molecularly targeted therapeutics into clinical practice has improved the prognosis of patients with clear-cell histology tumors. Based on published data from prospective phase III clinical trials, several drugs have been registered for advanced renal-cell carcinoma. Indications for different agents vary, however some of them overlap. Although similar in their mechanism of action, the agents differ in toxicity profiles, which is important because of long duration of palliative treatment and possibility of sequential use. All the factors considered, there is no single drug ensuring optimal treatment of every patient with the disease. In Poland, formal regulations reflecting a specific drug reimbursement policy lead to suboptimal treatment of some of the patients diagnosed with kidney cancer. The article presents a brief discussion of this issue.